One Health Interactions of Chagas Disease Vectors, Canid Hosts, and Human Residents along the Texas-Mexico Border. - Melissa N Garcia; Sarah O'Day; Susan Fisher-Hoch; Rodion Gorchakov; Ramiro Patino; Teresa P Feria Arroyo; Susan T Laing; Job E Lopez; Alexandra Ingber; Kathryn M Jones; Kristy O Murray (Public Library of Science (PLoS), 2016)
BACKGROUND:Chagas disease (Trypanosoma cruzi infection) is the leading cause of non-ischemic dilated cardiomyopathy in Latin America. Texas, particularly the southern region, has compounding factors that could contribute to T. cruzi transmission; however, epidemiologic studies are lacking. The aim of this study was to ascertain the prevalence of T. cruzi in three different mammalian species (coyotes, stray domestic dogs, and humans) and vectors (Triatoma species) to understand the burden of Chagas disease among sylvatic, peridomestic, and domestic cycles. METHODOLOGY/PRINCIPAL FINDINGS:To determine prevalence of infection, we tested sera from coyotes, stray domestic dogs housed in public shelters, and residents participating in related research studies and found 8%, 3.8%, and 0.36% positive for T. cruzi, respectively. PCR was used to determine the prevalence of T. cruzi DNA in vectors collected in peridomestic locations in the region, with 56.5% testing positive for the parasite, further confirming risk of transmission in the region. CONCLUSIONS/SIGNIFICANCE:Our findings contribute to the growing body of evidence for autochthonous Chagas disease transmission in south Texas. Considering this region has a population of 1.3 million, and up to 30% of T. cruzi infected individuals developing severe cardiac disease, it is imperative that we identify high risk groups for surveillance and treatment purposes.